The Effect of the Jurang Board Media (Addition and Substraction Board) on Early Numeracy Skills - Villa Parera; Darwin Effendi; Tuti Firdayani (Universitas Sebelas Maret, 2026)
Mathematics is one of the fundamental skills that is important for early childhood development. Good numeracy skills can serve as a foundation for more advanced academic abilities. This study aims to determine the effect of the jurang board media (addition and substraction board) on early numeracy skills in children aged 5-6 years. The method used was a pre-experimental design with an one-group pretest-posttest design. The research subjects consisted of 20 children selected through purposive sampling. Data were collected through prestest and posttest in the form of worksheet involving tasks such as recognizing numbers 1-10, coloring, and counting pictures of insects. Data collection techniques included tests, observations, and documentation. The results showed that the average pretest score was 34.60, while the average posttest score increased to 59.5. Hypothesis testing using the paired sample T-test showed a significance value of 0.000 (p<0.05), indicating a significant difference between the pretest and posttest scores. This study contributes to the development of engaging and interactive mathematics learning methods for children and encourages the use of creative media in early childhood education.